SUPPLEMENTARY LISTENING MATERIALS FOR UNDERGRADUATE STUDENTS: A PROTOTYPE OF DESKTOP AND MOBILE VERSION - Miranty, Delsa; Fargianti, Yusti; Anrika, Tania; Nurjanah, Eka (Jurnal Sistem Informasi, 2020)
Abstract - This research was intended to design a supplementary listening material that could help students to meet their needs in improving their listening skill. This materials would be build through an application that could be operated through personal computer or android. This research employed innovative work (R&D). It will follow the models of creating instructional materials which include Needs assessments, Product planning and design, Preliminary product development, Preliminary field testing, Product revision, Main field testing and Final product revision. [1] The objective of this study was to explain and describe the process of designing and using the supplementary listening material. In addition, this research was also aimed at finding out the influence of using the supplementary listening materials for undergraduate students. To answer the research questions, questionnaire and test were used as the instruments of the research to gain the data. Then the data were analyzed quantitatively by utilizing recurrence and rate. The most elevated rate were considered as the representation on the undergraduate condition. After that point, the recommendation and the remarks were dissected descriptively to decide the substance of the listening materials.Keywords – Android, Desktop, Supplementary Listening Materials, Undergraduate Students.